Penggunaan Konsep Regulatory Impact Assessment untuk Mencegah Praktik Otokratisme Hukum dalam Proses Pembentukan Peraturan Perundang-Undangan di Indonesia - Tarigan, Yefta Nikoyas; Agusmidah, Agusmidah (Peneliti.net, 2025)
The formation of laws and regulations in Indonesia in recent years has raised concerns regarding the rise of autocratic legalism—a practice where law is used as a tool to legitimize undemocratic power, often sidelining public participation and weakening checks and balances. This study aims to analyze the potential of applying the Regulatory Impact Assessment (RIA) framework as a means to prevent such practices in the legislative process. Using a normative juridical method with a conceptual and statutory approach, this research examines the alignment between current legislative mechanisms in Indonesia and the principles of RIA. The findings show that the absence of comprehensive stages such as policy option analysis, cost-benefit evaluation, and public consultation in Indonesia’s law-making process facilitates the emergence of autocratic legalism. By adopting RIA systematically, transparency, accountability, and inclusivity in the formation of legislation can be enhanced, thus safeguarding democratic governance and public interest.